The Relationship Between Islam and Adat in Indonesia a Comparison Between Java and Minangkabau - Soehardi Soehardi (Humaniora, 1997)
Islam has spread throughout Indonesia. since the thirteenth century, initially in Aceh and then gradually to the rest of Indonesia. Hitherto, nominally approximately 90% of the total population of Indonesia are Muslim. Presumably, the feature of the relationship between Islam and adat in Java and west Sumatra seems to be different. Here I shall compare the ethnic Javanese and the Minangkabau. The ethnic Javanese represent the majority population In Indonesia. Most consider themselves Muslims, but only a few conduct the Islamic sharia. On the other hand, the Minangkabau people are considered to be pious Muslim.